PENGARUH WORKING CAPITAL MANAGEMENT, INTELLECTUAL CAPITAL, DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS - Nita Chrisvianti; Saiful Anam; Dian Indrianto (Jurnal Trial Balance, 2025)
The aim of the research is to determine the influence of the variables Working Capital Management, Intellectual Capital, Company Size, Profitability. Population data includes manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2020 - 2023. The data sample used is the result of a purposive sampling technique and the number of samples suitable for use is 197 companies. During the research carried out, the method used was a quantitative method using the SPSS 24 program. Based on the results of testing by researchers, the variables that are known to influence profitability are Working Capital Management and Company Size which are positive and significant. However, the variable that has no effect on profitability is Intellectual Capital